Risk factors for short‐ and long‐term mortality in very old patients with Clostridium difficile infection: A retrospective study. Issue 10 (20th September 2016) - Leibovici‐Weissman, Yaara; Atamna, Alaa; Schlesinger, Agata; Eliakim‐Raz, Noa; Bishara, Jihad; Yahav, Dafna
Abstract : Aim: Most cases of Clostridium difficile infections (CDI) occur in patients aged 65 years and older. Older age is associated with increased mortality. Risk factors for mortality in patients aged 80 years and older are not well recognized. Methods: We analyzed retrospective data including 184 patients aged 80 years and older hospitalized with CDI during 2009–2014. We aimed to delineate risk factors for short‐ and long‐term mortality. Results: The 30‐day mortality was 33.2%; 1‐year mortality was 64.7%. Median survival was 110 days (interquartile range 24–655 days). All four patients who underwent colectomy died. Risk factors for 30‐day mortality in multivariate analysis were diabetes mellitus, low albumin and therapy other than metronidazole monotherapy, the latter probably reflecting higher severity of disease rather than a true predictor of mortality. Risk factors for long‐term mortality analyzed in Cox regression were albumin ≤2.5 g/dL (HR 0.58, 95% CI 0.395–0.850), presentation with sepsis (HR 0.597, 95% CI 0.408–0.873), a non‐independent activities of daily living baseline status (HR 0.460, 95% CI 0.236–‐0.897) and Charlson score (HR 0.867, 95% CI 0.801–0.938). None of the traditional severity indices for CDI (such as leukocytosis or creatinine increase) proved to be predictors of mortality over the age of 80 years. Conclusions: The prognosis of old patients with CDI is dismal. Considering the high mortality, efforts to prevent CDI should be first priority in patients aged 80 years and older. Assessment of albumin levels should be part of the evaluation at presentation and considered when choosing treatment, rather than standard severity indexes for CDI.Geriatr Gerontol Int 2017; 17: 1378–1383.